2007
DOI: 10.1371/journal.ppat.0030164
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor Mrr1p Controls Expression of the MDR1 Efflux Pump and Mediates Multidrug Resistance in Candida albicans

Abstract: Constitutive overexpression of the MDR1 (multidrug resistance) gene, which encodes a multidrug efflux pump of the major facilitator superfamily, is a frequent cause of resistance to fluconazole and other toxic compounds in clinical Candida albicans strains, but the mechanism of MDR1 upregulation has not been resolved. By genome-wide gene expression analysis we have identified a zinc cluster transcription factor, designated as MRR1 (multidrug resistance regulator), that was coordinately upregulated with MDR1 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
404
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 306 publications
(444 citation statements)
references
References 51 publications
35
404
2
3
Order By: Relevance
“…Tac1p was also shown to activate the transcription of CDR1 and CDR2 upon cell treatment with different compounds such as fluphenazine (FPZ) and steroids (estrogen, progesterone) (6), but the mechanisms by which these compounds trigger Tac1p activity are still unknown. Similarly, gain-of-function mutations in two other zinc cluster transcription factors, Mrr1p and Upc2p, have recently been shown to be responsible for the constitutive upregulation of Mdr1p and Erg11p, respectively, in clinical A r isolates (10,22). These data confirmed the involvement of different transcriptional pathways in the upregulation of the CDR1/CDR2, MDR1, and ERG11 genes in A r isolates.…”
supporting
confidence: 58%
“…Tac1p was also shown to activate the transcription of CDR1 and CDR2 upon cell treatment with different compounds such as fluphenazine (FPZ) and steroids (estrogen, progesterone) (6), but the mechanisms by which these compounds trigger Tac1p activity are still unknown. Similarly, gain-of-function mutations in two other zinc cluster transcription factors, Mrr1p and Upc2p, have recently been shown to be responsible for the constitutive upregulation of Mdr1p and Erg11p, respectively, in clinical A r isolates (10,22). These data confirmed the involvement of different transcriptional pathways in the upregulation of the CDR1/CDR2, MDR1, and ERG11 genes in A r isolates.…”
supporting
confidence: 58%
“…MRR1 was discovered by genome-wide transcriptional analysis of C. albicans isolates that up-regulated MDR1. Deletion of MRR1 in clinical strains blocked MDR1 up-regulation (Morschhauser et al 2007). Fifteen different MRR1 GOF mutations have been reported (Sanglard 2011;Eddouzi et al 2013), causing constitutive up-regulation of MDR1 (Dunkel et al 2008).…”
Section: Trans-acting Elementsmentioning
confidence: 97%
“…Nineteen different TAC1 mutations have been confirmed as GOF, whereas others remain candidates Siikala et al 2010;Sanglard 2011). The TAC1 regulon was further elucidated by genome-wide transcriptional profiling and DNA occupancy analysis of Tac1 (Liu et al 2007), demonstrating that Tac1 binds to the DRE of CDR1 and CDR2, likely via a consensus-binding motif (CGGN 4 CGG). Recently, another CDR1 regulator was discovered by systematic overexpression of modified Zn 2 Cys 6 genes; MRR2 (orf19.6182) is required for the basal expression of CDR1; however, it does not regulate CDR2 (Schillig and Morschhauser 2013).…”
Section: Trans-acting Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was proposed that drug resistance and the response to oxidative stress are interconnected processes in C. albicans (Znaidi et al, 2009). This connection exists through the activity of several TFs like Cap1p, Tac1p, Mrr1p or Upc2p for which (i) gain-of-function mutations were observed as being related to clinical azole resistance and (ii) genome-wide studies identified several of their target genes as being involved in the general response to oxidative stress Morschhauser et al, 2007;Znaidi et al, 2009;Znaidi et al, 2008). Also, it is interesting to remind that, in S. cerevisiae, YAP1 was initially described as a gene involved in pleiotropic drug resistance (Wu et al, 1993).…”
Section: Yap Proteins and The Response To Oxidative Stressmentioning
confidence: 99%